POLITIK MODERAT: Studi Pemikiran Muhammad Sa’id Ramadhan al-Buthi - Muhammad Wahdini (Jurnal Sosiologi Agama, 2020)
This paper discusses the thoughts of Muhammad Sa'id Ramadhan Al-Buthi in the political field. Al-Buthi is a figure that is considered by some to be controversial because it is close to the Al-Assad regime, which in fact the majority of scholars hate the Al-Assad regime which is considered wrong. This paper is the result of a study of several literary literature relating to Al-Buthi's political conception. In this case Al-Buthi places more emphasis on moderation which leads to the unity of a country. His socio-political experience in the struggle over political issues in Suriah led him to very moderate thinking. His rejection of the revolution and more agree with reform because of the comparative advantage of the two. Al-Buthi emphasizes more on how moderate politics he prioritizes the creation of unity in the state of the nation so that its benefits for citizens are met. In addition to his rejection of extreme ways of politics he also placed women's representation as part of a government